Optimalisasi Pengelolaan Asset Bergerak di Desa Margajaya Kecamatan Sukadana Kabupaten Ciamis - Rafiq Andra Wisudana; Neti Sunarti; Ii Sujai (Pusat Riset dan Inovasi Nasional, 2025)
This research is motivated by the existence of problems in the management of movable assets owned by Margajaya Village which are not yet optimal. The purpose of this study is to determine the optimization of movable asset management in Margajaya Village, Sukadana District, Ciamis Regency. The method used in this study is descriptive analysis. There are 6 informants. Data collection techniques are literature studies, field studies (observations and interviews) and documentation. The author uses qualitative data analysis techniques through processing data from interviews and observations to draw conclusions so that they can answer the problems in the study. Based on the results of the study, it is known that: Optimization of movable asset management in Margajaya Village has been implemented but has not been optimal in accordance with the principles of asset management, namely the functional principle, legal certainty, openness, efficiency, accountability, and certainty of value. This shows that the movable assets owned by the village have been used but have not been managed effectively to support the implementation of government duties and community services. There are several obstacles faced in the management of movable assets, including limited competent human resources, inadequate supporting facilities and infrastructure, lack of socialization and understanding of regulations, limited community participation in supervision, and budget constraints for asset maintenance and development. Efforts have been made by the Margajaya Village Government together with related parties to overcome these obstacles, including conducting training and increasing the capacity of village officials, implementing a digital-based asset management information system, socializing and assisting with asset management regulations, increasing transparency and community participation, and optimizing village budget management.